THE INFLUENCE OF JOB DESIGN AND REWARDS ON EMPLOYEE PERFORMANCE AT PT. WAHANA TATA INSURANCE MANADO - Mekel, Regina Cecilia; Tumbuan, Willem J.F Alfa (Universitas Sam Ratulangi, 2016)
Human resource department related to companyâ€™s employee positions, rewards, compensation, training, and managing employees benefit. It is the factors that human resource management do to improve employee performance to achieve companyâ€™s goals. Seeing the important things of human in achieving organizational goals, it is necessary for management system to managing the human resource. This research design to analyzed the influence of job design and rewards on employee performance at PT. Wahana Tata Insurance. In this study, all the respondents are the all employee at PT. Wahana Tata Insurance which are 35 respondents. This research use multiple regression analysis with quantitative method. Result and conclusion show that job design and rewards significantly influence on employee performance. Job design has partial and significant influence on employee performance. Rewards has partialÂ significant influence on employee performance. The management of PT. Wahana Tata Insurance must consider that job design influencing employee performance. It is important because job design will contribute a positive result to employee performance when the job design arrange well by the management. Then it suggested to the management to arrange and positioning all the employees at the best position. Keywords: job design, rewards, employee performance